Critical Analysis of the Islamic Criminal Law and International Humanitarian Law on the notion of Jus ad Bellum and Jus in Bello - Dr. Muhammad Asif Safdar; Dr Jamil Ahmad; Tariq Iqbal; Bilal Maqbool (Al Manhal Research Journal, 2025)
War has to be on just grounds. The theory of Just war is the hallmark of the armed conflict which is technically called Jus ad Bellum. Islamic law combines the concepts of jus ad bellum,the right to go to war and jus in bello the conduct of war whereas International Humanitarian Law (IHL) separates these two concepts and only applicable to the Jus in Bello. Islamic law requires that both the decision to go to war and the conduct of war must be just and in accordance with Islamic principles but IHL has no jurisdiction over the jus ad bellum which results into the narrow applicability of IHL rules on the contemporary armed conflicts and poses a gap which has to be bridged. This research article endeavors to propose extension of the jurisdiction of the Islamic Criminal Law to IHL statutory rules for inculcating the just war theory into the framework of IHL by including the Jus ad Bellum into the structure of IHL in consonance with the Islamic Criminal Law.